Testing the Effect of General Election on Market Reaction of Islamic vis-à-vis Conventional Capital Market: Does Presidential Election Cycle Theory Exist in Indonesia? - Rouf, Abdul; Muhammad Adnan (Global Review of Islamic Economics and Business, 2024)
This paper investigates the Presidential Election Cycle Theory by examining the Indonesian stock market's reaction to presidential elections from 2004 to 2024. Specifically, it compares the reactions of Islamic and conventional capital markets. Employing an event study methodology with abnormal return as the indicator, the analysis utilizes secondary data comprising daily stock prices for seven days preceding and following each election. The findings indicate that presidential elections have a significant effect on capital market reactions, as evidenced by abnormal return values. However, the Islamic capital market demonstrates greater resilience than its conventional counterpart in responding to political events, such as presidential elections. The study concludes that the Presidential Election Cycle Theory is applicable to Indonesia, necessitating its consideration by policymakers, investors, and all stakeholders.